PERSONALITY DAN IKLAN LAYANAN MASYARAKAT KEMENTERIAN KESEHATAN RI ANTI ROKOK DAN PERILAKU MEROKOK YANG MENGGANGU LINGKUNGAN - Emilkamayana Emikamayana (Program Studi Magister Manajemen Lingkungan, 2016)
The purpose of this study is to determine whether there is a relationship between personality and public service advertising Ministry of Health Anti-smoking with smoking behavior. The study was conducted in December to May 2013 in Sempaja Selatan Village with the number of samples used as many as 44 people with total population of male-male population in South Sempaja Sub-District of North Samarinda District. This study uses linear regression analysis with SPSS Program Version 16. The result of Analysis of Varians (ANOVA) is showed that it is no relation between personality and advertisement of anti smoking service with smoking behavior, because F value counted 1,239 with sig level. of 0.300, where this figure is greater than the sig level. 0.05. These results indicate that variable personality and anti-cigarette service public service advertising do not significantly affect smoking behavior in the community.